2017
DOI: 10.6090/jarq.51.363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wood Density and Water Content Between Dry Evergreen and Dry Deciduous Forest Trees in Central Cambodia

Abstract: We compared wood density (WD) and water content (WC) between a dry evergreen forest (DEF) and dry deciduous forest (DDF) in central Cambodia. Wood core samples of 53 species from DEF and 54 species from DDF were collected. Average WD and WC in all species were similar between DEF (0.64 g/cm 3 of WD; 0.40 g/cm 3 of WC) and DDF (0.64 g/cm 3 of WD; 0.42 g/cm 3 of WC), although the average WC of five tree species that appeared in both forest types was higher in DDF than that in DEF. Tree size effects on WD and WC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
3
7
0
2
Order By: Relevance
“…WD, a direct outcome of total lumen and wall fractions, was weakly or not related to fresh water content indices (Figure 6d and Figure S7d in Data S1), similar to previous studies of tropical and temperate angiosperms, representing a combined total of 573 species (Kenzo, Sano, Yoneda, & Chann, 2017;Kenzo, Tomoaki, Yuta, Joseph Jawa, & Sophal, 2016;Longuetaud et al, , 2017E. Suzuki, 1999).…”
Section: The Magnitude Of Capacitance and Water Storagesupporting
confidence: 88%
“…WD, a direct outcome of total lumen and wall fractions, was weakly or not related to fresh water content indices (Figure 6d and Figure S7d in Data S1), similar to previous studies of tropical and temperate angiosperms, representing a combined total of 573 species (Kenzo, Sano, Yoneda, & Chann, 2017;Kenzo, Tomoaki, Yuta, Joseph Jawa, & Sophal, 2016;Longuetaud et al, , 2017E. Suzuki, 1999).…”
Section: The Magnitude Of Capacitance and Water Storagesupporting
confidence: 88%
“…wood density and stiffness, which can be measured with pilodyn and FAKOPP, respectively, are used to measure the wood quality of solid and fiber products (Pilai et al 2013;Defo et al 2016;Ramananantoandro et al 2016). Our research showed that various dipterocarp species showed significantly different PP (Table 3) because of the differences in their phylogenetic group (Kenzo et al 2017) and the light requirement for their growth (King et al 2005;Van Gelder et al 2006;Rana et al 2009;Ramananantoandro et al 2016). The highest PP was observed in S. dasyphylla, S. leprosula, and S. parvifolia, which formed a group of light-demanding and light-hardwood dipterocarp species.…”
Section: Dbh Growth Pp An Swvmentioning
confidence: 66%
“…Furthermore, the size of DDF species has no effect on wood density, except S. obtusa Wall. that has a positive relationship between tree diameter and wood density [29]. Thus, drought resistance in DDF might be the results of the different strategies adopted in terms of the hydraulic and leaf phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high wood density species tends to have a relatively higher drought resistance compared to the low wood species [27,28]. In addition, a few studies in TDFs have indicated that leaf phenology is related to wood density [27,29]. However, the relationships between leaf phenology, wood density and its resistance to drought have not yet been investigated in the secondary DDF.…”
Section: Introductionmentioning
confidence: 99%